Biblijne podstawy personalizmu Karola Wojtyły = The biblical roots of Karol Wojtyla`s personalism - Szarlej, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper is devoted to the twentieth-century European associations of personality with the Bible. Although elements of the biblical tradition seem in this philosophy natural, acquired from the Christian tradition of both Protestant (e.g. Paul Tillich) and Catholic (e.g. Romano Guardini, Emmanuel Mounier, Karol Wojtyla) or even Jewish (e.g. Martin Buber) provenience, the convergence of the personalists` views with the expression of the specific biblical pericopes of both Old and New Testament is striking and calls for observation.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; personalizm; personalism